Analysis of Long Service Skills of Badminton PB Daun Muda Banjarbaru - Doni; Edwin Wahyu Dirgantoro; Mita Erliana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to analyze the analysis of basic long service badminton technique skills of PB Daun Muda Banjarbaru. The method used in this study is descriptive quantitative by analyzing the motion of long service badminton skills and the measurement test of long service badminton skills. The population in this study was 20 people and a sample of 10 people. With the sampling technique using the purposive technique (sample availability). The results of the study of the analysis of basic long service badminton technique skills of PB Daun Muda Banjarbaru, the category is very good 9 people (90%) and the category is less than 1 person (10%). The results of the long service badminton skills of PB Daun Muda Banjarbaru are in the very good category 8 people (80%) and the category is moderate 2 people (20%). The conclusion of the results of the study of the analysis of long service badminton movements of PB Daun Muda Banjarbaru is in the very good category and the long service skills of PB Daun Muda Banjarbaru are in the very good category.